(untitled) (Latakia University Journal -Medical Sciences Series, 2021)
The importance of the Hyoid Bone lies in its being not articulated with any other bone, but connects with Craniofacial bones via unique muscular system, in addition to be a link between Cranial and Mandibular structures. Several studies that have dealt with the issue of The Hyoid Bone ; were done using the Lateral Cephalometric Radiographs (LCR), so this study managed to be done using CBCT Scan, to get more accurate and reliable measurements. Objective: Evaluating the anterio-posterior and vertical position of the Hyoid Bone in the skeletal Class (I, II, III). Materials and Methods: The sample comprised (68 CBCT Scans) for Syrian adult individuals with permanent occlusion, aged between (12-28) years, whom never being under gone of orthodontic treatment before, but they were directed by groups other orthodontists to have CBCT Scans. The sample was divided into three groups: (skeletal Class I, skeletal Class II, skeletal Class III). ANOVA and Scheffe tests were applied to study the statistical significance between the three groups. Results: The Hyoid Bone takes a more forward position in skeltel CL II subjects comparing with their counterparts of skeletal CL I and CL III, and a more posterior position in skeletal CL III subjects comparing with their counterparts of skeletal CL I and CL II, and also a more lower position in skeletal CL I subjects comparing with their counterparts of skeletal CL I and CL III.